2021
DOI: 10.1016/j.heliyon.2021.e08618
|View full text |Cite
|
Sign up to set email alerts
|

Marine heatwaves of sea surface temperature off south Java

Abstract: The frequency of marine heatwaves (MHWs) events has been rising globally in recent years, and this trend is expected to continue in the region off the coast of south Java Island. These oceanic extreme events may have the potential to devastate marine habitats, ecosystems and fisheries. This paper characterized MHWs off south Java from 1982 to 2019 using satellite-observed sea surface temperature. The aim of this study was to examine the dynamics of MHWs in one of Indonesia's most important fisheries hotspots, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…2d, e, f). In accordance to our study, a previous study showed that the average maximum intensity in southern Java from January 1982 to December 2019 reached > 1.8 ℃ (Iskandar et al 2021). Interestingly, we found in the present study that the highest maximum intensity occurred during the warm phase of the PDO when El Niño dominated Indonesian waters (Fig.…”
Section: Characteristics Of Mhws In the Indonesian Waterssupporting
confidence: 93%
“…2d, e, f). In accordance to our study, a previous study showed that the average maximum intensity in southern Java from January 1982 to December 2019 reached > 1.8 ℃ (Iskandar et al 2021). Interestingly, we found in the present study that the highest maximum intensity occurred during the warm phase of the PDO when El Niño dominated Indonesian waters (Fig.…”
Section: Characteristics Of Mhws In the Indonesian Waterssupporting
confidence: 93%
“…Moreover, along the entire length of the BoB, MHWs tend to occur at nearly the same time. In this region, the intensity of MHWs is also predicted to increase 69 .…”
Section: Resultsmentioning
confidence: 97%
“…Located between two oceans, which are the Indian ocean and the Pacific ocean, the strength of the South Java upwelling can be affected by oceanic and atmospheric dynamics such as monsoons (Wyrtki, 1962;Duan et al, 2019), tides (Ffield and Gordon, 1996;Rudiastuti et al, 2019), the Madden-Julian Oscillation (MJO) (Duan et al, 2019), Kelvin and Rossby waves (Cipollini et al, 2001;Iskandar, 2005;Menezes and Vianna, 2019;Pujiana and McPhaden, 2020;Syamsudin, 2004), the Pacific to Indian ocean water masses flowing through the Indonesian archipelagos called the Indonesian Through Flow (ITF) (Cipollini et al, 2001;Menezes and Vianna, 2019), the South Java Coastal Current (SJCC) (Soeriaatmadja, 1957;Quadfasel & Cresswell, 1992;Sprintall et al, 1999;Gingele et al, 2002;Utari et al, 2019), South Equatorial Current (SEC) (Ningsih et al, 2020), eddies Yang et al, 2019;Ismail et al, 2021), marine heatwaves (Iskandar et al, 2021), the Indian Ocean Dipole (IOD) (Saji et al, 1999;Gualdi et al, 2003;Wirasatriya et al, 2020), and El Niño/Southern Oscillation (Susanto and Gordon, 2001; ENSO; e.g. Gualdi et al, 2003;Susanto et al, 2006).…”
Section: Introductionmentioning
confidence: 99%